Fishing, fish consumption, and knowledge about advisories in college students and others in central New Jersey - Burger, Joanna (Environmental research, 2005)
Risks to humans and other organisms from consuming fish have become a national concern. Over the past 3 years there have been a number of national advisories regarding saltwater fish. Although information on fishing, consumption patterns, and public knowledge about advisories has been examined for at-risk populations, there is little information about the latter for a general population. Overall knowledge about advisories, ratings for information about the risks and benefits of eating fish, and the relationship between fishing, consumption patterns, and knowledge about advisories was examined in a sample of 180 college students and others residing in central New Jersey, USA. The null hypothesis of no differences in fishing, consumption, and knowledge about advisories as a function of age, gender, ethnicity, and education was tested. A significantly higher proportion of men fished compared to women, and significantly fewer Blacks and Asians fished than did Whites or Hispanics. More Asians who fished did so in salt water, compared to others. There were no gender differences in consumption patterns, and few age or ethnic differences, mainly due to low sample sizes in some ethnic groups. Significantly fewer young people and fewer Asians ate fish compared to others. Overall, more people knew about the benefits of eating fish than the risks. Half as many people had heard about advisories concerning tuna, and less than a third knew about advisories concerning shark and swordfish than had heard general warnings. There were no gender differences in knowing about advisories, but there were several ethnic differences: a lower percentage of Asians generally knew that there were advisories, and fewer Blacks knew that there were benefits from eating fish than others. People in the age group 21–45 years were less aware of both the benefits and the risks from eating fish compared to older people. These data suggest that risk managers need to target younger people for information about the risks and benefits of consuming fish, particularly given that this is the population that will become pregnant over the next few years. Contrary to some previous research, subjects trusted family, friends, and other fishermen less for knowledge about the risks and benefits of fish consumption than other sources, such as doctors, governmental officials, and university professors. Even with this limited sample size, it is clear that people have heard more about the benefits of fish consumption than the risks, and a relatively low percentage have heard about the recent US Food and Drug Administration warnings about swordfish and shark.